Encapsulation of Bifidobacterium pseudocatenulatum strain G4 within bovine gelatin-genipin-sodium alginate combinations: optimisation approach using face central composition design-response surface methodology (FCCD-RSM) - Abdul Khalil, Khalilah; Mustafa, Suhaimi; Mohamad, Rosfarizan; Ariff, Arbakariya; Ahmad, Siti Aqlima; Dahalan, Farrah Aini; Abdul Manap, Mohd Yazid (Hindawi, 2019)
Bovine gelatin is a biopolymer which has good potential to be used in encapsulating matrices for probiotic candidate Bifidobacterium pseudocatenulatum strain G4 (G4) because of its amphoteric nature characteristic. Beads were prepared by the extrusion method using genipin and sodium alginate as a cross-linking agent. The optimisation of bovine gelatin-genipin-sodium alginate combinations was carried out using face central composition design (FCCD) to investigate G4 beads’ strength, before and after exposed to simulated gastric (SGF), intestinal fluids (SIF), and encapsulation yield. A result of ANOVA and the polynomial regression model revealed the combinations of all three factors have a significant effect () on the bead strength. Meanwhile, for G4 encapsulation yield, only genipin showed less significant effect on the response. However, the use of this matrix remained due to the intermolecular cross-linking ability with bovine gelatin. Optimum compositions of bovine gelatin-genipin-sodium alginate were obtained at 11.21% (w/v), 1.96 mM, and 2.60% (w/v), respectively. A model was validated for accurate prediction of the response and showed no significant difference () with experimental values.